The Medieval Town and Port of Damā (As Sib) on the Southern al-Bāținah Plain, Oman: Archaeological Fieldwork of the Italian-German-Omani Project in 2013 - Loreto, Romolo; Hoffmann, Göesta; Berardino, Simona; Priestman, Seth; Gajewska, Maria; Kennet, Derek; al-Motrāshi, Isma'il (The Journal of Oman Studies, 2025)
In May 2013 Gõesta Hoffmann and Maurizio Tosi had the opportunity to document some surface clusters of Islamic period remains in the wilayät Sib, along the coastal area between Wadi Al Lawami and Wadi Al Khars. This consisted mainly of pottery dated between the early to late Islamic period (8th to 20th centuries CE). In June 2013, on behalf of the then Ministry of Ileritage and Culture, a first survey allowed us to recognise more archaeological materials focused around al-Rawdah Roundabout and the remains of a fort made of mudbricks and heavily obliterated by vegetation further to the south. In light of written sources referring to the ancient settlement of Damă as located in the southern al-Bäținah plain probably identifiable as As Sib (Seeb), further field analyses were undetaken in September 2013 in order to define the geoarchacological landscape via systematic survey, investigative excavations, and the definition of the palco coastline pertaining to the fort. The results of the project support the hypothesis that the ancient town and harbour of Dama is indeed to be located in present day As Sib.